Efektifitas Pemberian Buah Pisang Ambon dan Buah Kurma Terhadap Kadar Hemoglobin Pada Ibu Hamil Dengan Anemia - Fatmawati Ibrahim; Rahma Dewi Agustini; Desak Made Yulianti (Politeknik Kesehatan Kemenkes Mamuju, 2026)
Anemia in pregnant women is a health problem that can increase the risk of complications for the mother and fetus. Efforts to improve hemoglobin (Hb) levels can be carried out through pharmacological and non-pharmacological approaches, including the consumption of fruits rich in iron. This study aims to analyze the effectiveness of giving Ambon bananas and dates on improving hemoglobin levels in pregnant women with anemia. This study used a quasi-experimental design with a pre-post test with control group approach. The sample consisted of 32 pregnant women with anemia who were divided into two groups, namely the intervention group (Fe + Ambon bananas) and the control group (Fe + dates). The intervention was given for 14 days, with Hb levels measured before and after treatment. The results of the Wilcoxon test showed a significant increase in Hb levels in both groups (p < 0.05). The results of the Mann-Whitney test showed that the increase in Hb levels in the Fe + dates group was higher compared to the Fe + Ambon bananas group (p < 0.05). The conclusion of this study shows that the consumption of dates is more effective than Ambon bananas in increasing hemoglobin levels in pregnant women with anemia.